Development of efficient solar cells with the use of multifunctional multitextures - Yerokhov, Valerij; Ierokhova, Olga (Eastern-European Journal of Enterprise Technologies, 2017)
Here we demonstrate the prospects of creating a solar cells using the hybrid technologies of obtaining multifunctional multitextures of porous silicon (PS) to the frontal surface. We conducted analysis of the existing models of PSand selected the models, most suitable for the creation of microtexture. We theoretically examined the relationship between the diameter of pore dP, porosity P and the region of specific surface S. On the samples with high specific resistance, we explored the interaction between porosity P(t) and the region of specific surface S(t) of the PS grown by the electrochemical etching of silicon substrates. Depending on the technological parameters, it is possible to form the layers of macro-, micro- or nanopores. Multifunctional multitextures were fabricated on the frontal surface of photoelectric converters (SC). VAC were measured by the spectral conditions AM 1,5G, experiments for both samples of SC were carried out on the silicon substrates with the same parameters and area. SC parameters were confirmed by the volt-ampere characteristics of SC and resulting measurements of efficiency in the obtained SC and spectral characteristics. Spectral characteristic for the multitexture in the range of 400–1150 nm has a significant feature; it practically has no high values in the infrared range. This significantly reduces the integral coefficient of reflectivity for the frontal surface multitexture of SC 7 %, different from other integral coefficients of reflectivity. For the chemical texture 17.5 %, random pyramids 11.2 %, for the polished surface of Si – larger than 35 %.